Trick or treat? Maternal involuntary job loss and children's non-cognitive skills - Frauke H. Peter (Deutsches Institut für Wirtschaftsforschung (DIW), 2013)
Negative effects of job loss on adults such as considerable fall in income have long been examined. If job loss has negative consequences for adults, it may spread to their children. But potential effects on children's non-cognitive skills and the related mechanisms have been less examined. This paper uses propensity score matching to analyze maternal involuntary job loss and its potential causal effect on children's non-cognitive skills. Job loss is defined as end of employment either due to plant closure or due to dismissals by employer. Using a rich and representative data set, the German Socio-Economic Panel Study (SOEP), I estimate associations of maternal job loss on child outcomes for preschool children aged five/six and for adolescents aged seventeen. The paper analyses influences on children's socio-emotional behavior and on adolescents' locus of control. The obtained results show that children whose mothers experience an involuntary job loss are more likely to have behavioral problems and are less likely to believe in self-determination.
Keywords: J13; J63; J65; 330; child development; maternal job loss; non-cognitive skills; propensity score matching